Polyvinyl Alcohol/Chitosan/Silicon Dioxide (PVA/CS/Sio2) Beads For Removal Of Chromium (VI) Ions / Rizamarhaiza Muda...[et al.] - Muda, Rizamarhaiza; Sulaiman, Syazwan Liyana; Ahmad, Sufizar; Mohd Taib, Hariati (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Chromium pollution has become a global issue and many techniques have been developed for the removal of Chromium (Cr) VI ions from wastewater. In this study, blended polymer absorbent beads which was polyvinyl alcohol/chitosan/silicon dioxide (PVA/CS/SiO2) beads were prepared by a dropwise method by crosslinking of sodium hydroxide, ethanol and glutaraldehyde in aqueous solution. The varied concentration of CS from 0.5 to 2.5g and concentration of SiO2 from 0 to 1.0g. All of the samples of crosslinked PVA/CS/SiO2 beads were put under UV irradiation for two hours in Cr(VI) solution. Analyses performed on the beads were by Atomic Absorption Spectroscopy (AAS), Scanning Electron Microscopy (SEM) and Energy Dispersive X-Ray Spectroscopy (EDX) analysis. Moreover, in the pH value for each sample before and after the absorption test also has been measured. Beads morphology images showed that all of the samples of PVA/CS/SiO2 beads revealed macro and micro pores on the surface of beads before the Cr(VI) absorption and the pore size increased with the increment of CS and SiO2 concentration. The surface of beads that became smooth after Cr(VI) absorption, indicated that the pores on the surface were filled up with Cr. This is further supported by the EDX analysis which evidently shows Cr peaks. The results of pH value of Cr after the absorption test showed that lowest pH value of 5.81 and highest pH value of 6.08. The absorption of Cr(VI) in the PVA/CS/SiO2 beads was found to be in the range of 90% and above , as analyzed by the AAS technique. Thus it can be concluded that the use of PVA/CS/SiO2 beads is indeed significant for eliminating Cr(VI) from industrial wastewater.